Rascovan, S., Levy, D. y Korinfeld, D. - Lozano, Adriana Beatríz; Castro, Vanina Anabella (Praxis Educativa, 2014)
Entre Adolescentes y Adultos en la Escuela. Puntuaciones de época Editorial Paidós (2014)